Efficacy of Rational Emotive Therapy in the Management of Antisocial Personality Disorder among Adolescents in Owerri Municipal, Imo State, Nigeria - Agbakwuru, Chikwe; Mgbeoduru, Hope Ejiociii (Advances in Social Sciences Research Journal, 2020)
This study investigated the efficacy of Rational Emotive Therapy in, the management of (ASPD) among adolescents in Owerri municipal, Imo State, Nigeria. It adopted a quasi-experimental design of pre-test post-test control group. Three research questions and three hypotheses tested at 0.05 level of significance guided the study. Thirty adolescents who were eighteen years formed the sample. Mean, standard derivation, t-test and 2 ways ANOVA were used to analyze the data obtained. The results obtained showed that Rational Emotive Therapy is efficacious in the management of antisocial personality disorder at post and follow up tests. The results also indicate that male and female adolescents have ASPD and are amenable to change using cognitive restructuring technique of Rational Emotive Therapy. Based on the findings, it was recommended that counselling psychologists should be posted to schools and made teaching subject free to enable them identify and work on adolescents with ASPD and its antecedents of Attention Deficit Hyperactivity Disorder, Oppositional Defiant Disorder and Conduct Disorders.